In vivo dynamics of chromatin-associated complex formation in mammalian nucleotide excision repair - Moné, Martijn J. (National Academy of Sciences, 2004)
Chromatin is the substrate for many processes in the cell nucleus, including transcription, replication, and various DNA repair systems, all of which require the formation of multiprotein machineries on the chromatin fiber. We have analyzed the kinetics of in vivo assembly of the protein complex that is responsible for nucleotide excision repair (NER) in mammalian cells. Assembly is initiated by UV irradiation of a small area of the cell nucleus, after which the accumulation of GFP-tagged NER proteins in the DNA-damaged area is measured, reflecting the establishment of the dual-incision complex. The dynamic behavior of two NER proteins, ERCC1-XPF and TFIIH, was studied in detail. Results show that the repair complex is assembled with a rate of ≈30 complexes per second and is not diffusion limited. Furthermore, we provide in vivo evidence that not only binding of TFIIH, but also its helicase activity, is required for the recruitment of ERCC1-XPF. These studies give quantitative insight into the de novo assembly of a chromatin-associated protein complex in living cells.